The Establishment Of Legislation Using Omnibus Law As A Legal Breakthrough By The Government - Ahmad Muzayyin S; Muhammad Khairil Anwar; M. Yusuf Habiby; Tria Septiana (Faculty of Law, University of Mataram, 2022)
Legislation and the process of its formation have a significant function in the development of national law. In Indonesia, legislation is the main method of creating law and the foundation of the national legal system. However, Indonesia is currently having hyperregulation. This article aims to describe the omnibus law method as a legal breakthrough used in the framework of establishing legislation. The discussion shows that omnibus law is the accurate method to be used as a solution in structuring laws and regulations. To overcome hyperregulation in Indonesia, the government chose the Omnibus law method, which is a legal breakthrough by forming new laws that amend, delete, and or/make new provisions from various laws. Law Number 11 of 2020 concerning Job Creation is a law that establishes using the omnibus method by changing, deleting, and or making new provisions from various laws.